2014
DOI: 10.1097/sla.0000000000000239
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Topography of Lymph Node Metastases in Early Esophageal and Gastric Cancer

Abstract: Risk estimation for lymph node metastases should not be based on depth of tumor infiltration alone but additional clinicopathological parameters should also be considered. The extent of lymphadenectomy in surgical procedures should respect the presented topography of lymph node metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
54
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 33 publications
11
54
1
Order By: Relevance
“…Degiuli et al [37] found 17/189 (9 %) patients with three or more positive lymph nodes in their randomised controlled trial of lymphadenectomy had early gastric cancer. Other surgeons have reported positive N3 lymph nodes in patients labelled as having early gastric cancer [38,39]. If lymph node status was known, there would be significant change in the management of these patients.…”
Section: Early Gastric Cancer: the Definitions And Issuesmentioning
confidence: 97%
See 2 more Smart Citations
“…Degiuli et al [37] found 17/189 (9 %) patients with three or more positive lymph nodes in their randomised controlled trial of lymphadenectomy had early gastric cancer. Other surgeons have reported positive N3 lymph nodes in patients labelled as having early gastric cancer [38,39]. If lymph node status was known, there would be significant change in the management of these patients.…”
Section: Early Gastric Cancer: the Definitions And Issuesmentioning
confidence: 97%
“…Given that the indications for therapeutic endoscopy do not take into account lymph node status, it appears reasonable that, at the very least, lymphovascular invasion be considered. Two recent approaches to predicting lymph node metastases have taken lymphovascular invasion into account [38,80]. Shida et al [80] looked to predict lymph node metastases [38] proposed a nomogram to predict the risk of lymph node metastases in early gastric and oesophageal cancers using multiple factors, including age, tumour depth and differentiation, tumour multi-focality and lymphovascular invasion.…”
Section: Redefining Early Gastric Cancer: the Way Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…In association with T stage, LN involvement can be found in 15% of patients with carcinoma confined to the mucosa, whereas LN metastases were detected in 23.4%, 48.2%, and 69.8% of patients with carcinoma invading the submucosa, muscularis propria and serous layer, respectively [14] Gertler et al [15] showed that not only infiltration of the submucosa but also lymphatic vessel invasion, multifocal tumor growth, younger patient age and poor tumor differentiation were associated with nodal disease. Besides T stage, LN involvement can also be influenced by tumor size.…”
Section: Ln Involvementmentioning
confidence: 99%
“…There is a very high prevalence of affected LN in cases of LVI, poor differentiation [35][36][37][38] and in the diffuse type of adenocarcinoma with a size of >2 cm [39][40][41]. In the case of verified LN metastasis, surgery and chemotherapy in the adjuvant setting represent the treatment of choice [42].…”
Section: Early Gastric Lesionsmentioning
confidence: 99%